2.45 GHz microwave radiation induced oxidative and nitrosative stress mediated testicular apoptosis: Involvement of a p53 dependent bax‐caspase‐3 mediated pathway. Issue 9 (3rd July 2018) - Shahin, Saba; Singh, Surya Pal; Chaturvedi, Chandra Mohini
Abstract: Deleterious effects of MW radiation on the male reproduction are well studied. Previous reports although suggest that 2.45 GHz MW irradiation induced oxidative and nitrosative stress adversely affects the male reproductive function but the detailed molecular mechanism occurring behind it has yet to be elucidated. The aim of present study was to investigate the underlying detailed pathway of the testicular apoptosis induced by free radical load and redox imbalance due to 2.45 GHz MW radiation exposure and the degree of severity along with the increased exposure duration. Twelve‐week old male mice were exposed to 2.45 GHz MW radiation [continuous‐wave (CW) with overall average Power density of 0.0248 mW/cm 2 and overall average whole body SAR value of 0.0146 W/kg] for 2 hr/day over a period of 15, 30, and 60 days. Testicular histology, serum testosterone, ROS, NO, MDA level, activity of antioxidant enzymes, expression of pro‐apoptotic proteins (p53 and Bax), anti‐apoptotic proteins (Bcl‐2 and Bcl‐xL ), cytochrome‐c, inactive/active caspase‐3, and uncleaved PARP‐1 were evaluated. Findings suggest that 2.45 GHz MW radiation exposure induced testicular redox imbalance not only leads to enhanced testicular apoptosis via p53 dependent Bax‐caspase‐3 mediated pathway, but also increases the degree of apoptotic severity in a duration dependent manner.